2014
DOI: 10.1097/dad.0b013e3182a74c7a
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Case Series of Indolent Small/Medium-Sized CD8+ Lymphoid Proliferations With Predilection for the Ear and Face

Abstract: We report 7 cases of a CD8 lymphoid proliferation of the ear and face with a cytotoxic T-cell phenotype, but an indolent clinical course. All patients presented with stable or slowly growing asymptomatic lesions on the ear, nose, or lower eyelid. Histopathology showed a dense diffuse dermal infiltrate of small- to medium-sized atypical lymphocytes without destructive features. The lymphocytes were positive for CD3, CD8, β-F1, and TIA-1 and negative for CD4, CD30, CD56, granzyme B, and PD-1. Of note, the prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Primary cutaneous acral CD8+ T‐cell lymphoma (acral CD8+ TCL) is a rare and indolent lymphoma that was classified as provisional entity in the 2016 revision of the World Health Organization (WHO) classification of tumors of hematopoietic and lymphoid tissue . It is clinically characterized by single or (less frequently) multiple nodules or plaques similar to those of primary cutaneous CD4+ small/medium T‐cell lymphoproliferative disorders without any evidence of a T follicular helper phenotype . It was first described as indolent lymphoid proliferation of the ear, but later reports described the presence of lesions at other, usually facial, acral sites; extra‐facial skin involvement is also described .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cutaneous acral CD8+ T‐cell lymphoma (acral CD8+ TCL) is a rare and indolent lymphoma that was classified as provisional entity in the 2016 revision of the World Health Organization (WHO) classification of tumors of hematopoietic and lymphoid tissue . It is clinically characterized by single or (less frequently) multiple nodules or plaques similar to those of primary cutaneous CD4+ small/medium T‐cell lymphoproliferative disorders without any evidence of a T follicular helper phenotype . It was first described as indolent lymphoid proliferation of the ear, but later reports described the presence of lesions at other, usually facial, acral sites; extra‐facial skin involvement is also described .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is histologically characterized by monomorphic blast‐like cells with a CD8+ cytotoxic phenotype, acral CD8+ TCL is prognostically different from aggressive CD8+ lymphomas such as primary cutaneous aggressive epidermotropic CD8+ cytotoxic T‐cell lymphoma (pcAETCLs) and CD8+ peripheral T‐cell lymphoma, not otherwise specified (PTL‐NOS). Cutaneous relapses are possible, but systemic progression has never been reported before …”
Section: Introductionmentioning
confidence: 99%
“…Although patients with CD8+ LP in our study were not evaluated for PD-1, previous studies have shown absence of follicular T- cell markers, suggesting different cells of origin in the two entities. 6 The proliferation index was low (median 15%) in all CD4+ SMPTCL and CD8+LP cases as expected for an indolent disease process.…”
Section: Discussionmentioning
confidence: 53%
“…This recently described entity presents with slow growth of solitary cutaneous papules and nodules, usually located on the ear (Fig 9A) but subsequent cases have been presented on the nose, hands and feet (Greenblatt et al, 2013;Li et al, 2014). Histologically, this condition is characterized by a non-epidermotropic, monotonous, dermal infiltrate composed by medium-sized T-cells with a Grenz zone (Fig 9B, C).…”
Section: Cutaneous Gamma/delta T-cell Lymphoma (Cgdtcl)mentioning
confidence: 99%